Bose and his Movement : From Nazi Germany to French Indochina - More, J.B.P., (Brill | Manohar Publishers & Distributors, 2022)
The work is based on original sources in the archives and libraries of France, England, India and Vietnam. It recounts the activities of Subhas Chandra Bose and his freedom movement in Germany and brings out certain hidden features of his life as found in the records, with adequate supporting evidence. The study also elaborates on Bose's activities in Southeast Asia, with a special focus on French Indochina. Incidentally it was from Saigon that he disappears from the face of the world. After rejecting the air crash theory in which Bose was supposed to have died as well as the Russian escape theory as untenable for want of factual evidence, the study concludes that Bose never left Saigon or Indochina after 17 August 1945, where he died in mysterious circumstances, before the arrival of the Cabinet Mission to India. The war treasures of Bose were confiscated by the Allied troops in Saigon during a search operation.